ANALISIS PERPUTARAN PERSEDIAAN BAHAN BAKU FOOD AND BEVERAGE DEPARTEMEN DI ASTON BATAM HOTEL AND RESIDENCE - Martogi Hasudungan Tamba; Lise Asnur (Ensiklopedia of Journal, 2023)
The research was conducted because the author found a problem about inventory turnover in the raw materials of the food and beverage departemen. So this study aims to analyze the inventory turnover of raw materials for the food and beverage departemen at Aston Batam hotel and Residences. The type of this research is qualitative  with descriptive approach. The informants of this study were 5 experts in the turnover of  food raw material inventory with a type of non probality sampling with purpose sampling technique. Data collection techniques are interviews, observation, and documentation. Data analysis technique consist of data reduction, data presentation, conclusion drawing, and inventory turnover analysis. The results of this study are an analysis of the inventory turnover of raw materials for the food and beverage departemen with a normal inventory turnover method of 20 times and an inventory turnover day method of 2-8 times, with a stable inventory turnover system, handling of raw materials has a procedure, by following storage requirements and applying FIFO (first in first out) techniques and the inventory turnover day method makes it easier for staff to identify the demand patterns of each outlet and manage existing inventory when inventory.